Midblock signalled pedestrian crossing : alternative controller algorithms - Chik, Abdul Aziz; Ismail, Che Ros; Hainin, Mohd. Rosli (Faculty of Civil Engineering, UTM, 2000)
Observation at midblock signalled pedestrian crossings in Malaysia showed that violation of the red signal aspect by both the motorists and pedestrians is close to 70 %. Motorists may travel on the red signal aspect when there is no pedestrian on the crossing. Pedestrians are also observed to cross in vehicle gaps at the crossings during the right of way to vehicles. Such behaviour is dangerous especially at a system where the traffic movements rely on the signal aspects shown to them. Four alternative algorithms were designed in order to enhance the operation and safety of users at the midblock signalled pedestrian crossings in Malaysia. The objectives are to increase pedestrian safety and drivers compliance with the signal. The developed strategies required detectors to register the vehicle and pedestrian demands. Algorithms were designed to compute the appropriate time to start and terminate the vehicle and pedestrian precedence. The applied computation aimed to limit vehicle delay and to ensure that vehicle saturation flow does not exceed 85 % of the road capacity. Apart from the vehicle demands, the developed strategies also attempt to emphasis on the requirement and limits of pedestrian behaviour. Four measures of performance are compared and evaluated. These measures are the percentage of vehicles crossing on the red man, pedestrian mean delay, mean cycle times and vehicle mean delay. The measures of performance of all algorithms are evaluated using a fully calibrated and validated simulation program. All of the new strategies increase the pedestrian compliance and balance. This indicates that the present system does not respond satisfactorily to the gaps in vehicle flow and may contribute to the users disrespect of the system.